Chelate Coordination Strengthens Surface Termination to Attain High‐Efficiency Perovskite Solar Cells. Issue 12 (27th October 2022) - Liu, Jiali; Yang, Tengteng; Xu, Zhuo; Zhao, Wangen; Yang, Yan; Fang, Yuankun; Zhang, Lu; Zhang, Jingru; Yuan, Ningyi; Ding, Jianning; Liu, Shengzhong (Frank)
Abstract: Solar cell efficiency and stability are two key metrics to determine whether a photovoltaic device is viable for commercial applications. The surface termination of the perovskite layer plays a pivotal role in not only the photoelectric conversion efficiency (PCE) but also the stability of assembled perovskite solar cells (PSCs). Herein, a strong chelate coordination bond is designed to terminate the surface of the perovskite absorber layer. On the one hand, the ligand anions bind with Pb cations via a bidentate chelating bond to restrict the ion migration, and the chelate surface termination changes the surface from hydrophilic to hydrophobic. Both are beneficial to improving the long‐term stability. On the other hand, the formation of the chelating bonding effectively eliminates the deep‐level defects including PbI and Pb clusters on the Pb‐I and FA‐I terminations, respectively, as confirmed by theoretical simulation and experimental results. Consequently, the PCE is increased to 24.52%, open circuit voltage to 1.19 V, and fill factor to 81.53%; all three are among the highest for hybrid perovskite cells. The present strategy provides a straightforward means to enhance both the PCE and long‐term stability of PSCs. Abstract : A strong chelate coordination bond is designed to terminate the surface of the perovskite absorber layer. The formation of the chelate bond not only alters the tolerance of the perovskite film to high humidity but also results in weak ion migration, thus enhancing the long‐term stability and power conversion efficiency.